(untitled) (Web of Teachers: Inderscience Research, 2025)
The process of classroom management is very important and responsible for every teacher. Especially in subjects taught in a foreign language, such as English, classroom management and the correct definition of its basic principles are of great importance for increasing the effectiveness of learning and teaching English. In classroom management, the principles of discipline, motivation and communication coexist and are closely related to each other. These principles help the English teacher to successfully carry out his work, actively participate in the lesson process and, most importantly, master knowledge.